Towards a fibrous composite with dynamically controlled stiffness: lessons from echinoderms. (August 2000) - Trotter, J. A.; Tipper, J.; Lyons-Levy, G.; Chino, K.; Heuer, A. H.; Liu, Z.; Mrksich, M.; Hodneland, C.; Dillmore, W. S.; Koob, T. J.; Koob-Emunds, M. M.; Kadler, K.; et al.
Abstract : Sea urchins and sea cucumbers, like other echinoderms, control the tensile properties of their connective tissues by regulating stress transfer between collagen fibrils. The collagen fibrils are spindle-shaped and up to 1 mm long with a constant aspect ratio of approx. 2000. They are organized into a tissue by an elastomeric network of fibrillin microfibrils. Interactions between the fibrils are regulated by soluble macromolecules that are secreted by local, neurally controlled, effector cells. We are characterizing the non-linear viscoelastic properties of sea cucumber dermis under different conditions, as well as the structures, molecules and molecular interactions that determine its properties. In addition, we are developing reagents that will bind covalently to fibril surfaces and reversibly form cross-links with other reagents, resulting in a chemically controlled stress-transfer capacity. The information being developed will lead to the design and construction of a synthetic analogue composed of fibres in an elastomeric matrix that contains photo- or electro-sensitive reagents that reversibly form interfibrillar cross-links.